2013
DOI: 10.1159/000357052
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of an Intravenous to Subcutaneous Epoetin α Conversion

Abstract: Background/Aims: A cost analysis of a conversion from intravenous (IV) to subcutaneous (SC) epoetin α in patients receiving chronic in-center hemodialysis (HD). Methods: This retrospective analysis compared epoetin α drug costs during a 6-month period of IV usage (July to December 2010, period 1) to a 6-month period of SC usage (July to December 2011, period 2) in four large in-center HD units. Data were collected from quarterly counts of HD patients receiving epoetin α and monthly inventory billing records. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…SC epoetin was associated with a yearly cost savings of US$1135 per patient. 48 A meta-analysis by Besarab et al concluded that the cost of epoetin was reduced substantially when administered via route of SC in comparison to IV. 49 SC epoetin is twice as efficient as IV epoetin for the treatment of anemia in hemodialysis patients, with a dose saving of 53% ( P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…SC epoetin was associated with a yearly cost savings of US$1135 per patient. 48 A meta-analysis by Besarab et al concluded that the cost of epoetin was reduced substantially when administered via route of SC in comparison to IV. 49 SC epoetin is twice as efficient as IV epoetin for the treatment of anemia in hemodialysis patients, with a dose saving of 53% ( P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the routine use of the IV route by HD staff [16] as well as the issue of pain or 'stinging' or discomfort at the injection site associated with the initial use of SC epoetin-alfa which some studies have cited in the past [42]. The KDIGO guidelines have also cited 'pain' secondary to SC administration, in terms of using short-acting ESAs, as a reason to prefer IV EPO administration, referring to the results of a single centre trial of 30 patients [8,26]. In a randomized, un-blinded trial carried out by Kaufman et al among 208 patients, 86% of the 107 candidates who received SC epoetin injections reported experiencing pain as none to mild [43].…”
Section: Convenience Of Drug Administrationmentioning
confidence: 99%
“…For non-HD patients, the SC route may be more generally convenient due to the lack of a continuous IV access, the ease of self administration, comparatively lower dosage, less frequent hospital visits, a reduced dosing frequency and ultimately reduced costs. Even in HD patients, the SC route has been tied to similar advantages and may therefore be more beneficial overall as compared to the IV route, despite the obvious convenience that an arteriovenous fistula confers to IV EPO administration [ 13 - 17 , 19 , 26 - 28 , 31 - 35 ]. This may be particularly beneficial in low-income countries where affordability and access to newer, longer acting ESAs may be difficult [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…The financial and safety concerns with ESA use have resulted in implementation of ESA-related cost management programs, primarily in the outpatient setting, with varying degrees of success. Programs have focused on converting ESAs from intravenous (IV) to subcutaneous (SubQ) administration [ 14 ], converting from a shorter acting to a longer acting ESA (e.g. epoetin alfa to darbepoetin alfa) [ 15 ], implementing nurse-driven anemia management protocols [ 16 ], pharmacist-managed ESA clinics, pharmacist-led management protocols [ 17 , 18 ], and other strategies [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%